Petrel extinction in Macaronesia (North-East Atlantic Ocean): the case of the genus Pterodroma (Aves: Procellariiformes: Procellariidae) - Rando, J. Carlos; Pieper, Harald; Pereira, Fernando; Torres-Roig, Enric; Alcover, Josep Antoni (Zoological Journal of the Linnean Society, 2024)
The Late Quaternary fossil record indicates that formerly in the North Atlantic volcanic Macaronesian archipelagos (Azores, Madeira, Selvagens, Canary Islands, and Cape Verde) there was a higher avian diversity, including numerous now extinct species. Currently, only three gadfly petrels (genus Pterodroma) remain in two archipelagos: the Fea's petrel, Pt. feae, in Cape Verde (islands of Santiago, Fogo, Santo Antão, and São Nicolau); the Zino's petrel of Madeira, Pt. madeira, on the island of Madeira; and the Desertas petrel, Pt. deserta, on the islet of Bugio (Desertas Islands, Madeira Archipelago). Herein we describe the former distribution of the genus in Macaronesia based on the palaeontological record. However, the original specific diversity cannot be accurately established through the biometry of their fossil bones but the fossil record of Pterodroma in Macaronesia indicates: (i) its former presence in all Macaronesian archipelagos; (ii) the extinction of at least 16 island populations (73% of its original distribution on these islands); and (iii) the extinction of, at least, one species from Azores, here named Pterodroma zinorum sp. nov. Radiocarbon dates indicate than this species was still alive at sometime among 1104 and 1672 CE, documenting its extinction in the last millennium. This paper is a result of the Research Projects CGL2012-38087 and CGL2016-79795R, ‘Cambios holocénicos en la biodiversidad animal de las islas de la Macaronesia y de Baleares I and II’ funded by the Agencia Estatal de Investigación (Ministerio de Economía, Industria y Competitividad) Fondo Europeo de Desarrollo Económico y Regional (Dirección General de Investigación Científica y Técnica, Ministerio de Economía y Competitividad). In addition, J.C.R. was funded by a research grant from the Spanish Ministry of Science, Innovation and Universities, and the European Regional Development Fund (PID2022-140091NB-I00). Peer reviewed